Hubungan Disiplin Belajar dan Lingkungan Belajar dengan Prestasi Belajar Pendidikan Agama Islam dan Budi Pekerti Pada Siswa SMAN 1 Kapoiala Kabupaten Konawe - Samrin Samrin (Shautut Tarbiyah, 2016)
This study examines the relationship discipline of learning and the learning environment to the learning achievement of Islamic religious education and morality in students of SMAN 1 Kapoiala Kab. Konawe. This study aims to analyze empirically the relationship discipline of learning and the learning environment on student achievement SMAN 1 Kapoiala Kab. Konawe. The population in this study were students of SMAN 1 Kapoiala totaled 225. The samples in this study were taken by using random sampling (random sampling), with a sample of 69 students. Collecting data in this study using a questionnaire method of documentation. Data collected were analyzed by using descriptive and regression techniques. The results showed that the students' discipline included in either category 59.8%, the learning environment of students included in either category 59.82%, and the learning achievement of Islamic religious education and moral included in the category enough 54.5%. There is a positive and significant relationship between disiplinbelajar and learning environment on student achievement in the subject of Islamic religious education and moral in SMAN 1 Kapoiala the academic year 2014/2015 either partially or simultan.Berdasarkan study and discussion, we can conclude that there is a relationship antaradisiplin positive and significant learning and the learning environment to the learning achievement of Islamic religious education and moral either partially or simultaneously. Partially, the relationship given by the variable learning discipline by 34.40%, 25.80% of the learning environment. While it simultaneously hubungankedua magnitude of these variables is 45.5%.Keywords:      Discipline Learning, Learning Environment, Learning Achievement